Phyto-synthesis of CuO nano-particles and its catalytic application in C-S bond formation - Priya, Duraipandi Devi; Roopan, Selvaraj Mohana; Singh, Sehajpreet; Bansal, Jatin; Shanavas, Shajahan; Khan, Maksudur R.; Al-Dhabi, Naif Abdullah; Arasu, Mariadhas Valan; Duraipandiyan, Veeramuthu (Elsevier Ltd, 2020)
Inside the current examination, we examined the phyto-synthesis of CuO nanoparticles (CuO NPs) using Indigofera tinetoria (I. tinetoria). UV–Vis absorption spectroscopy was utilized to screen the stepwise development of CuO NPs. Transmission Electron Microscopy (TEM) analysis revealed the formation of nanoparticles in spherical shapes varying in size from 10 to 30 nm. The catalytic effects of the CuO NPs were tested in Carbon-Sulfur bond forming reaction. The synthesised organic moiety was affirmed using FT-IR, 1H NMR, and 13C NMR and GC–MS examinations.